The characterization of purified recombinant fragment B as a tool to study diphtheria toxin - Manoilov, K.Yu.; Gorbatiuk, O.B.; Usenko, M.O.; Shatursky, O.Ya.; Borisova, T.A.; Kolibo, D.V.; Komisarenko, S.V. (Reports of the National Academy of Sciences of Ukraine, 2017)
The purification of recombinant diphtheria toxin (DT) derivative, fragment or subunit B (SbB) synthesized in cytoplasm, periplasm, and solid inclusion bodies of E.coli, by metal-affinity chromatography following the enzymatic digestion of bacterial cell walls and DNA allowed us to avoid the contamination by endogenous poreforming proteins. The recombinant DT derivatives, SbB, and CRM197 are shown to bind the receptors of DTsusceptible cells Vero and non-susceptible cells L929 with equal affinity. The introduction of SbB (0.3 μg/ml) at positive voltages from the side of a phosphatidylethanolamine-containing bilayer membrane, where the derivative was added, results in the creation of potential-dependent ionic channels with the conductance of 20 pS in the bathing solution of 1M KCl buffered at pH 4.8 as had been shown in the classic studies of wild-type DT. The comparative analysis has shown that the channel-forming abilities of wild-type DT are best reproduced by SbB synthesized in the non-active form of inclusion bodies and renaturated in vitro.